When Leadership Inspires: Exploring the Influence of Democratic Leadership and Work Motivation on Lecturer Success - Rabiatul Monawarah; Akhmad Fauzi Hamzah (Managere: Indonesian Journal of Educational Management, 2025)
Lecturer performance is a strategic factor in improving the quality of higher education, which is not only determined by individual competence, but also by the leadership environment that oversees it. This study aims to analyze the influence of democratic leadership style on lecturers' performance with work motivation as a mediating variable. The research design used is quantitative with an explanatory research approach. The research population consisted of 27 permanent lecturers in the Arabic Language Education Study Program at STIQ Amuntai, all of whom were sampled using saturated sampling techniques. Data were collected using a five-point Likert scale questionnaire, accompanied by observation and documentation. Path analysis is used to test the relationships between variables, accompanied by the Sobel test to confirm the mediation effect. The results of the study show that the democratic leadership style has a significant effect on the work motivation and performance of lecturers, both directly and through the mediation effect of work motivation. The implications of these findings confirm the importance of implementing participatory leadership in the university environment as a strategy to enhance work motivation, improve lecturer performance, and promote the achievement of sustainable educational quality standards.